2017
DOI: 10.2174/1389201018666171026155522
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxic Effects and Production of Cytokines Induced by the Endophytic Paenibacillus polymyxa RNC-D In Vitro

Abstract: Our data suggest that the TLE of P. polymyxa RNC-D modulated the production of cytokines with different patterns of immune response in a dose-dependent way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Our results showed that the values of EC 50 obtained in the periods of 24 and 48 hours of leishmanicidal were 0.624 mg/mL and 0.547 mg/mL, respectively ( Table 1 ). Neris and collaborators [ 24 ] have previously observed the effect of the Paenibacillus polymyxa RNC-D extract in BALB/3T3 fibroblasts and J774A.1 macrophages. In the present study, it was reported that the mortality rate of 50% was around 1.171 mg/mL for fibroblasts and 0.994 mg/mL for macrophages in the period of 48 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the values of EC 50 obtained in the periods of 24 and 48 hours of leishmanicidal were 0.624 mg/mL and 0.547 mg/mL, respectively ( Table 1 ). Neris and collaborators [ 24 ] have previously observed the effect of the Paenibacillus polymyxa RNC-D extract in BALB/3T3 fibroblasts and J774A.1 macrophages. In the present study, it was reported that the mortality rate of 50% was around 1.171 mg/mL for fibroblasts and 0.994 mg/mL for macrophages in the period of 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that there was significant production of IL-12 in the infected group treated with 0.5 mg/mL ( Figure 2(d) ). For the other concentrations of the extract (0.1 and 1 mg/mL), there was no significant production of this cytokine, which may be the result of the regulation of IL-10, since significant production of NO was observed in the periods of 24 and 48 hours in macrophages exposed to the extract [ 24 ].…”
Section: Discussionmentioning
confidence: 99%